Pengaruh Jumlah Uang Beredar, Ekspor dan Impor Terhadap Inflasi (Studi Empiris Pada Perekonomian Indonesia) - Jumhur, Jumhur; Nasrun, Muhammad Ali; Agustiar, Memet; Wahyudi, Wahyudi (Fakultas Ekonomi dan Bisnis, UNTAN, 2018)
This research aims to analyze the influence of money supply, export, and import on inflation rate in Indonesia. It employs multiple regression method to analyze a time series data between 1985 and 2016. The findings showed that money supply positively and significantly influences inflation rate; export positively and significantly influences inflation rate; and import positively influences inflation yet not significantly. These findings illustrate that Indonesia inflation is also caused by both internal (money supply) and external factors (export and import). Therefore, a policy to stabilize inflation rate shall be formulated by considering both internal and external influences.